Marriage from the Perspective of Child Protection Law and Human Rights - Erma Hari Alijana (Annujum: Journal of Humaniora and Law, 2026)
This study analyzes the effectiveness of legal protection for children against early marriage in Indonesia, examining the issue through the lenses of human rights and family law. Despite the 2019 amendment to the Marriage Law raising the minimum age to 19, child marriage remains prevalent due to significant regulatory disharmony and judicial loopholes. Employing a normative-juridical method supported by empirical socio-legal data, this research investigates the conflict between the Child Protection Law and other statutes regarding the age of majority. The findings demonstrate that the "marriage dispensation" mechanism, intended for emergencies, is systematically exploited to legitimize underage unions, often driven by unintended pregnancies and parental pressure. Consequently, the state inadvertently facilitates violations of children's rights to development and safety. The study concludes that legal reform alone is inadequate; eradicating child marriage requires a synchronized strategy involving stricter judicial audits on dispensation requests, harmonization of conflicting laws, and comprehensive community engagement to dismantle patriarchal norms. This research underscores the urgency of shifting from a purely regulatory approach to a holistic, victim-centered protection framework that prioritizes the child's best interests.